Implementation Of Local Wisdom Values In Learning As An Effort To Strengthen A Caring Attitude To The Environment Through The Content Analysis Methode - Wulandari, Dian; Nurhayati, Nunung; Setiawan, Asep Rudini (Universitas Pakuan, 2024)
This study aims to describe the research results on implementing local wisdom in learning the character of caring for the Environment. These findings will look for new ways, especially the benefits of local wisdom in learning that can increase environmental awareness. The research method uses content analysis of the 2016-2023 articles from Google Scholar, Crossref, and Garuda, which explore using the keywords local wisdom learning and environmental care. The finding shows that using local wisdom in the learning process can strengthen the character of caring for the Environment. The benefits of implementing local wisdom in the learning process can increase environmental awareness, learning based on local wisdom has a significant effect on increasing motivation, participation, and creativity in developing environmental learning media; students are more enthusiastic about participating in the learning process outside the classroom, and are stimulated to think about and connecting culture with learning science. In addition, learning based on local wisdom can increase curiosity, increase mastery of the material, apply concepts and foster attitudes and character of caring for the environment. Through local wisdom students can create contextual learning, be able to change attitudes, skills, behavioral values and beliefs about nature and make students literate, have character and conservation agents